Persepsi Mahasiswa Terhadap Pelaksanaan Pembelajaran Berbasis Riset Pada Materi Perpindahan Kalor - Budi, Gunarjo Suryanto; Farcis, Fenno; Hartanto, Theo Jhoni; Siloam, Kristanoval; Putri, Umi Amanda (FKIP Universitas Palangka Raya, 2025)
Physics is one of the subjects that plays a role in developing analytical, critical, inductive, and deductive skills in problem-solving through a scientific approach. However, various studies reveal that this subject is less popular because many students perceive it as abstract, difficult to understand, and less relevant to everyday life, resulting in a low understanding of physics concepts. This study aims to explore students' perceptions of the implementation of research-based learning in the heat transfer material. The research subjects were 20 students enrolled in the Thermodynamics course of the Physics Education Study Program at FKIP, University of Palangka Raya. The instrument used was a perception questionnaire. The results showed that students had a positive perception of their learning experience using a research-based approach. Based on these findings, research-based learning can be considered an alternative strategy for more meaningful learning, especially in physics education.